Iraq in Fragments : The Occupation and its Legacy - Herring, Eric and Rangwala, Glen (London Hurst & Comany, 2006)
Explains that the nature of US state building in Iraq has created incentives for unregulated local power struggles and patron-client relations. Placing the occupation within the context of regional, global and US politics, this work demonstrates how the politics of co-option, coercion and economic change have transformed the lives of Iraqi people.
Include Maps, Notes and Index
Keywords: Iraq -- Iraq War (2003-2011) -- Politics and government